Dinamika Preventif Pencegahan Gangguan Psikologis Siswa Sekolah Dasar Korban Kekerasan Seksual - Susandi, Ari; Irmaningrum, Rizka Novi; Kharisma, Ahmad Ipmawan; Zativalen, Oriza (Universitas Negeri Surabaya, 2024)
The aim of this research is to describe the preventive dynamics of preventing psychological disorders in elementary school students who are victims of sexual violence. The research approach used is a qualitative approach with research methods in the form of descriptive research methods. The data sources taken are the results of interviews, observations, journals, articles, books and other scientific works that are relevant and in accordance with the object of research study. The data collection techniques used were observation, interviews and documentation. Data analysis uses analysis from Miles and Huberman. The results of the research show that there is an impact of psychological disorders on students who are victims of sexual violence, namely Betrayal. Trust is the main basis for victims of sexual violence. Sexual trauma (Traumatic sexualization) victims who experience sexual violence tend to become individuals who will refuse and oppose their responsibilities, feeling helpless (Powerlessness). The feeling of helplessness arises due to fear in the victim's life. Nightmares, phobias and anxiety experienced by victims are accompanied by pain, stigmatization. Sexual violence can make victims feel guilty, ashamed, and have a bad self-image. Guilt and shame are formed due to helplessness and feeling that they do not have the power to control themselves.